High-dispersion and full-biodegradation black dyeing master batch containing modified lignin and preparation method of high-dispersion and full-biodegradation black dyeing master batch
By using modified lignin to replace part of carbon black in black masterbatch, the problem of uneven dispersion of carbon black is solved, and the black masterbatch with high dispersion, uniform dyeing and full biodegradation is achieved, which improves the biochar content and the performance of plastic products.
Patent Information
- Application Number
- CN202411881645.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-19
- Publication Date
- 2025-03-28
AI Technical Summary
In the prior art, after adding carbon black with a content of more than 20-40%, the carbon black will agglomerate, resulting in uneven dispersion of carbon black in the black masterbatch, affecting the consistency of blackness and mechanical properties of plastic products.
Modified lignin is used to replace part of carbon black as pigment and serve as a dispersant for carbon black and degradable resin to promote compatibility between inorganic fillers and resins, thereby improving biocarbon content and dispersion.
The black masterbatch with high dispersion, uniform dyeing, and fully biodegradable has achieved a black masterbatch, and its mechanical properties and appearance meet the requirements, and can replace part of the carbon black to increase the content of biochar.
Abstract
Description
Technical Field
[0001] The invention belongs to the field of degradable plastic products, and specifically relates to a highly dispersed and fully biodegradable black dyeing masterbatch containing modified lignin and a preparation method thereof. Background Art
[0003] With the release of plastic restriction orders in various provinces, biodegradable plastics have become popular materials, among which PLA, PBSA and PBAT are several representative raw materials. After degradation, they generate water and carbon dioxide, and are environmentally friendly materials. At the same time, PBSA and PBAT are suitable for processing technologies such as film blowing and injection molding. For the sake of beauty, garbage bags are generally made black, so it is necessary to add black masterbatch during the preparation process. The existing black masterbatch on the market is a black masterbatch based on PE, which cannot be completely biodegraded. Moreover, after adding more than 20-40% of carbon black in the prior art, carbon black will agglomerate, resulting in uneven dispersion of carbon black in the black masterbatch, making the plastic products obtained in the subsequent film blowing or injection molding process uneven in blackness, and the blackness and brightness of some positions do not meet the requirements, thereby affecting the mechanical properties and appearance of the final product.
[0004] Therefore, in view of the current status of resource utilization and the shortcomings in plastic products, the present invention aims to provide a raw material composition of a highly dispersed, fully biodegradable black masterbatch containing lignin and a preparation method thereof. The black masterbatch component structure contains renewable natural high-molecular lignin, and has the advantages of good dispersibility, uniform dyeing, and full biodegradability. Summary of the invention
[0005] The problem to be solved by the present invention is to use renewable, non-toxic and harmless lignin to replace part of carbon black as a pigment to prepare a black masterbatch with good dispersibility, uniform dyeing, high dyeing efficiency and full biodegradability. In addition, the modified lignin is also used as a dispersant for carbon black and degradable resin to promote the compatibility between inorganic fillers and resins, which can not only increase the biocarbon content, but also be comparable to the black masterbatch with all carbon black added.
[0006] The present invention adopts the following technical solutions to solve the above technical problems.
[0007] A highly dispersed, fully biodegradable black dyeing masterbatch containing modified lignin, wherein the weight percentages of the components in the raw materials for preparing the masterbatch are: 40-70 parts of a degradable carrier, 20-50 parts of carbon black, 20-40 parts of modified lignin, 2-4 parts of a plasticizer, 2-4 parts of a dispersant, 1-3 parts of an antioxidant, and 2-5 parts of a coupling agent;
[0008] The modified lignin is obtained by subjecting natural lignin to a hydrogen peroxide chain-breaking treatment and then to a hydrothermal treatment at high temperature and high pressure for a certain period of time, and the median particle size D50 is 10-50 microns.
[0009] Preferably, the natural lignin comprises one or more of groundwood lignin (MWL), alkali lignin (AL), Klason lignin (KL), solvent-based alcoholysed lignin (OEL), pre-watered liquid lignin, lignin sulfonate, and enzymatically hydrolyzed lignin.
[0010] Preferably, the amount of hydrogen peroxide used is 1-5% of the absolute dry weight of lignin.
[0011] Preferably, the hydrothermal treatment temperature is 120-240° C., and the hydrothermal treatment time is 1-6 h.
[0012] Preferably, the degradable carrier is a mixture of polylactic acid (PLA) and polybutylene terephthalate adipate (PBAT) in a weight ratio of 1:1-1:20.
[0013] Preferably, the carbon black is nanoscale carbon black, and its particle size is 100-800nm.
[0014] Preferably, the plasticizer includes one or more of acetyl tributyl citrate, tributyl citrate, and trioctyl citrate.
[0015] Preferably, the dispersant includes one or both of TAS-2 and TAS-2A.
[0016] Preferably, the antioxidant is a food grade antioxidant, including one or more of hindered phenol antioxidants 1010, 1076 and phosphite antioxidants 168, 626.
[0017] Preferably, the coupling agent is one or two of silane coupling agents, including one or more of vinyltrimethylsilane, vinyltri(β-methoxyethoxy)silane and vinyltrimethoxysilane.
[0018] The present invention also provides a method for preparing a highly dispersed, fully biodegradable black dyeing masterbatch containing modified lignin, which specifically comprises the following steps:
[0019] (1) All materials are mixed in a high-speed mixer to obtain uniform material A;
[0020] (2) Material A is put into an internal mixer for internal mixing at a certain temperature for a certain period of time to obtain material B;
[0021] (3) Material B is refined into thin sheets at a certain temperature on a mixing mill to obtain material C;
[0022] (4) The material C is crushed on a crusher to obtain material D;
[0023] (5) The material D is extruded and granulated on a twin-screw extruder, and the temperature of each zone is controlled within a certain temperature range to obtain a highly dispersed, fully biodegradable black masterbatch containing lignin.
[0024] Preferably, in step (2), the banburying temperature is 120-160° C. and the time is 5-20 min.
[0025] Preferably, in the step (3), the refining temperature is 50-100° C., and the refining is performed 1-3 times.
[0026] Preferably, in step (5), the temperature of each zone of the twin-screw extruder is controlled within the range of 110 to 185°C.
[0027] The present invention also provides a highly dispersed and fully biodegradable black dyeing masterbatch containing lignin, which is prepared by the above preparation method.
[0028] On the basis of being in accordance with the common sense in the art, the above-mentioned preferred conditions can be arbitrarily combined to obtain the preferred embodiments of the present invention.
[0029] The reagents and raw materials used in the present invention are commercially available.
[0030] The positive and progressive effects of the present invention are: the highly dispersed and fully biodegradable black masterbatch containing lignin prepared by the present invention is a part of the main raw material of natural polymer with a wide range of renewable sources, which can realize the efficient utilization of resources and turn waste into treasure; at the same time, it can replace a part of carbon black to increase the content of biochar, has degradability, is very friendly to the environment, and its dispersibility, dyeability, and dosage are comparable to commercially available degradable black masterbatch and PE black masterbatch. In addition, the modified lignin described in the present invention has a smaller particle size, better compatibility with rubber, and the mechanical properties of the obtained rubber product are better. DETAILED DESCRIPTION
[0031] The present invention is further described in conjunction with the following examples, but the protection scope of the present invention is not limited thereto. Explanation for the examples: The raw materials used in the following examples are not limited to the raw materials required for this application, and are only used for writing the examples.
[0032] Example 1
[0033] A highly dispersed, fully biodegradable black dyeing masterbatch containing modified lignin and a preparation method thereof, specifically comprising the following steps:
[0034] (1) 910 g PBAT, 50 g PLA, 480 g carbon black, 240 g solvent-based alcoholysis lignin modified sample (solvent-based lignin was hydrothermally treated at 200° C. for 3 hours with 2% hydrogen peroxide added, filtered, washed, dried, and crushed into fine powder with a median particle size D50 of 10 μm), 32 g trioctyl citrate, 32 g TAS-2, 16 g antioxidant 1010, and 32 g vinyltrimethylsilane were mixed in a high-speed mixer to obtain a uniform material A;
[0035] (2) Material A is put into an internal mixer for internal mixing at 130° C. for 10 min to obtain material B;
[0036] (3) Material B is smelted once on an open mill at 50° C. into thin flakes to obtain material C;
[0037] (4) The material C is crushed on a crusher to obtain material D;
[0038] (5) The material D is extruded and granulated on a twin-screw extruder, and the temperature of each zone is controlled within the range of 110-175° C., thereby obtaining a highly dispersed, fully biodegradable black masterbatch containing lignin.
[0039] Example 2
[0040] A highly dispersed, fully biodegradable black dyeing masterbatch containing modified lignin and a preparation method thereof, specifically comprising the following steps:
[0041] (1) 800 g PBAT, 160 g PLA, 560 g carbon black, 240 g alkali lignin modified sample (alkali lignin was hydrothermally treated at 220° C. for 2 hours with 5% hydrogen peroxide, filtered, washed, dried, and crushed into fine powder with a median particle size D50 of 20 μm), 18 g acetyl tributyl citrate, 48 g TAS-2A, 32 g antioxidant 1076, and 48 g vinyl trimethylsilane were mixed in a high-speed mixer to obtain a uniform material A;
[0042] (2) Material A was put into an internal mixer for internal mixing at 140° C. for 15 min to obtain material B;
[0043] (3) Material B is smelted once on an open mill at 80° C. into thin flakes to obtain material C;
[0044] (4) The material C is crushed on a crusher to obtain material D;
[0045] (5) The material D is extruded and granulated on a twin-screw extruder, and the temperature of each zone is controlled within the range of 110-175° C., thereby obtaining a highly dispersed, fully biodegradable black masterbatch containing lignin.
[0046] Example 3
[0047] A highly dispersed, fully biodegradable black dyeing masterbatch containing modified lignin and a preparation method thereof, specifically comprising the following steps:
[0048] (1) 1000 g PBAT, 120 g PLA, 480 g carbon black, 480 g lignin sulfonate modified sample (alkali lignin was hydrothermally treated at 240° C. for 6 hours with 1% hydrogen peroxide added, filtered, washed, dried, and crushed into fine powder with a median particle size D50 of 30 μm), 32 g trioctyl citrate, 32 g TAS-2, 16 g antioxidant, and 64 g vinyl triethoxysilane were mixed in a high-speed mixer to obtain a uniform material A;
[0049] (2) Material A is put into an internal mixer for internal mixing at 120° C. for 15 min to obtain material B;
[0050] (3) Material B is smelted twice on an open mill at 50° C. into thin flakes to obtain material C;
[0051] (4) The material C is crushed on a crusher to obtain material D;
[0052] (5) The material D is extruded and granulated on a twin-screw extruder, and the temperature of each zone is controlled within the range of 110-175° C., thereby obtaining a highly dispersed, fully biodegradable black masterbatch containing lignin.
[0053] Example 4
[0054] A highly dispersed, fully biodegradable black dyeing masterbatch containing modified lignin and a preparation method thereof, specifically comprising the following steps:
[0055] (1) 800 g PBAT, 100 g PLA, 480 g carbon black, 240 g lignin sulfonate modified sample (lignin sulfonate was hydrothermally treated at 240° C. for 1 hour under the condition of adding 3% hydrogen peroxide, filtered, washed, dried, and crushed into fine powder with a median particle size D50 of 50 μm), 48 g tributyl citrate, 32 g TAS-2, 16 g antioxidant 168, and 64 g vinyl tri(β-methoxyethoxy) silane were mixed in a high-speed mixer to obtain a uniform material A;
[0056] (2) Material A was put into an internal mixer for internal mixing at 145° C. for 10 min to obtain material B;
[0057] (3) Material B is smelted once on an open mill at 80° C. into thin flakes to obtain material C;
[0058] (4) The material C is crushed on a crusher to obtain material D;
[0059] (5) The material D is extruded and granulated on a twin-screw extruder, and the temperature of each zone is controlled within the range of 110-175° C., thereby obtaining a highly dispersed, fully biodegradable black masterbatch containing lignin.
[0060] Comparative Example 1
[0061] Compared with Example 1, the difference is that no modified lignin is added in step (1), and other condition parameters are the same as Example 1.
[0062] Comparative Example 2
[0063] Compared with Example 1, the difference is that 240 g of carbon black is added in step (1), and no modified lignin is added. Other conditions and parameters are the same as in Example 1.
[0064] Comparative Example 3
[0065] Compared with Example 1, the difference is that no silane coupling agent is added in step (1), and other conditions and parameters are the same as in Example 1.
[0066] Comparative Example 4
[0067] Compared with Example 1, the difference is that unmodified lignin is added in step (1), and other condition parameters are the same as Example 1.
[0068] Implementation effect:
[0069] The fully biodegradable black masterbatch prepared in Examples 1-4 and Comparative Examples 1-4 was weighed and added to PBAT resin (weight average molecular weight 150000, melt index (190°C, 2.16kg) 2.8g / 10min), the amount of black masterbatch added was 5%, and then a film with a thickness of 1 filament was blown at 185°C to test the dispersion color point (the number of color points with a particle size greater than 10μm) and the transmittance. At the same time, the Zhongyi black masterbatch was selected as a comparative sample.
[0070] Table 1. Dispersion and transmittance test results
[0071] <![CDATA[Number of color dots / m 2 > Light transmittance / % Comparison sample 10 9.21 Example 1 10 9.11 Example 2 9 8.45 Example 3 8 8.56 Example 4 8 8.69 Comparative Example 1 8 17.20 Comparative Example 2 18 7.88 Comparative Example 3 45 13.45 Comparative Example 4 27 13.23
[0072] It can be seen from the data in Table 1 that compared with the fully biodegradable black masterbatches prepared in Comparative Examples 1-4, the fully biodegradable black masterbatches prepared in Examples 1-4 have the advantages of good dispersibility and suitable light transmittance.
[0073] The above shows and describes the basic principles, main features and advantages of the present invention. It should be understood by those skilled in the art that the present invention is not limited by the above embodiments. The above embodiments and descriptions are only for explaining the principles of the present invention. Without departing from the spirit and scope of the present invention, the present invention may have various changes and improvements, which fall within the scope of the present invention to be protected. The scope of the present invention to be protected is defined by the attached claims and their equivalents.
Claims
1. A highly dispersed, fully biodegradable black dyeing masterbatch containing modified lignin, characterized in that: The mass proportions of the components in the raw materials for its preparation are: 40-70 parts of degradable carrier, 20-50 parts of carbon black, 20-40 parts of modified lignin, 2-4 parts of plasticizer, 2-4 parts of dispersant, 1-3 parts of antioxidant, and 2-5 parts of coupling agent; The modified lignin is obtained by subjecting natural lignin to a hydrogen peroxide chain-breaking treatment and then to a hydrothermal treatment at high temperature and high pressure for a certain period of time, and the median particle size D50 is 10-50 microns.
2. A highly dispersed, fully biodegradable black dyeing masterbatch containing modified lignin as claimed in claim 1, characterized in that: The natural lignin includes one or more of ground wood lignin (MWL), alkali lignin (AL), Klason lignin (KL), solvent-based alcoholysis lignin (OEL), pre-watered liquid lignin, lignin sulfonate, and enzymatic lignin.
3. The highly dispersed, fully biodegradable black dyeing masterbatch containing modified lignin according to claim 1, characterized in that: The amount of hydrogen peroxide used is 1-5% of the absolute dry weight of natural lignin.
4. The highly dispersed, fully biodegradable black dyeing masterbatch containing modified lignin according to claim 1, characterized in that: The hydrothermal treatment temperature is 120-240° C., and the hydrothermal treatment time is 1-6 hours.
5. The highly dispersed, fully biodegradable black dyeing masterbatch containing modified lignin according to claim 1, characterized in that: The degradable carrier is a mixture of polylactic acid (PLA) and polybutylene adipate terephthalate (PBAT), and the weight ratio thereof is 1:1-1:
20.
6. The highly dispersed, fully biodegradable black dyeing masterbatch containing modified lignin according to claim 1, characterized in that: The carbon black is nano-scale carbon black, and its particle size is 100-800nm.
7. The highly dispersed, fully biodegradable black dyeing masterbatch containing modified lignin according to claim 1, characterized in that: The plasticizer includes one or two of acetyl tributyl citrate, tributyl citrate, and trioctyl citrate; The dispersant includes one or both of TAS-2 and TAS-2A; The antioxidant is a food grade antioxidant, including one or more of hindered phenol antioxidants 1010, 1076 and phosphite antioxidants 168, 626; The coupling agent is one or two of silane coupling agents, including one or more of vinyl trimethyl silane, vinyl tri (β-methoxyethoxy) silane and vinyl trimethoxy silane.
8. A method for preparing a highly dispersed, fully biodegradable black dyeing masterbatch containing modified lignin according to any one of claims 1 to 7, characterized in that: The specific steps include: (1) All materials are mixed in a high-speed mixer to obtain uniform material A; (2) Material A is put into an internal mixer for internal mixing at a certain temperature for a certain period of time to obtain material B; (3) Material B is refined into thin sheets at a certain temperature on a mixing mill to obtain material C; (4) The material C is crushed on a crusher to obtain material D; (5) The material D is extruded and granulated on a twin-screw extruder, and the temperature of each zone is controlled within a certain temperature range to obtain a highly dispersed, fully biodegradable black masterbatch containing lignin.
9. The method for preparing a highly dispersed, fully biodegradable black dyeing masterbatch containing modified lignin according to claim 8, characterized in that: In the step (2), the banburying temperature is 120-160° C. and the time is 5-20 min; In the step (3), the refining temperature is 50-100° C. and the refining is performed 1-3 times; In the step (5), the temperature of each zone of the twin-screw extruder is controlled within the range of 110 to 185°C.
10. A highly dispersed, fully biodegradable black dyeing masterbatch containing modified lignin, characterized in that: Prepared according to the preparation method described in claims 8-9.